Multicultural Education as an Alternative to Countering Radicalism in the Era of Globalization: Thoughts of Prof Muhammad Tholchah Hasan - Rahma, Fina; Sabiq, Fairuz (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This research discusses multicultural education as an alternative to counter radicalism in the era of globalization based on the ideas of Prof. Mohammad Tolchah Hasan. This study aims to explore Prof. Mohammad Tolchah Hasan's ideas and identify multicultural education concepts that can be a solution to counter radicalism in the era of globalization. This research uses a qualitative descriptive method by analyzing Prof. Hasan Mohammad Tolchah Hasan's writings and related literature. The results show that Prof. Mohammad Tolchah Hasan emphasizes the importance of multicultural education as a solution to counter radicalism in the era of globalization. Prof. Mohammad Tolchah Hasan emphasized multicultural education concepts, including understanding differences, respecting diversity, and strengthening national identity. In addition, multicultural education can enhance critical thinking skills, tolerance, and empathy. However, implementing multicultural education in Indonesia still needs to overcome various obstacles, such as a lack of support from the government and society and problems in the curriculum and teaching. Therefore, joint efforts from the government, educational institutions, and society are needed to strengthen the implementation of multicultural education as an alternative to counter radicalism in the era of globalization.